Integrated control strategies for dengue, Zika, and Chikungunya virus infections - Côrtes, Nelson; Lira, Aline; Prates-Syed, Wasim; Dinis Silva, Jaqueline; Vuitika, Larissa; Cabral-Miranda, William; Durães-Carvalho, Ricardo; Balan, Andrea; Cabral-Marques, Otavio; Cabral-Miranda, Gustavo (Frontiers in Immunology, 2023)
Arboviruses are a major threat to public health in tropical regions, encompassing over 534 distinct species, with 134 capable of causing diseases in humans. These viruses are transmitted through arthropod vectors that cause symptoms such as fever, headache, joint pains, and rash, in addition to more serious cases that can lead to death.Among the arboviruses, dengue virus stands out as the most prevalent, annually affecting approximately 16.2 million individuals solely in the Americas. Furthermore, the re-emergence of the Zika virus and the recurrent outbreaks of chikungunya in Africa, Asia, Europe, and the Americas, with one million cases reported annually, underscore the urgency of addressing this public health challenge. In this manuscript we discuss the epidemiology, viral structure, pathogenicity and integrated control strategies to combat arboviruses, and the most used tools, such as vaccines, monoclonal antibodies, treatment, etc., in addition to presenting future perspectives for the control of arboviruses. Currently, specific medications for treating arbovirus infections are lacking, and symptom management remains the primary approach. However, promising advancements have been made in certain treatments, such as Chloroquine, Niclosamide, and Isatin derivatives, which have demonstrated notable antiviral properties against these arboviruses in vitro and in vivo experiments. Additionally, various strategies within vector control approaches have shown significant promise in reducing arbovirus transmission rates. These encompass public education initiatives, targeted insecticide applications, and innovative approaches like manipulating mosquito bacterial symbionts, such as Wolbachia. In conclusion, combatting the global threat of arbovirus diseases needs a comprehensive approach integrating antiviral research, vaccination, and vector control. The continued efforts of research communities, alongside collaborative partnerships with public health authorities, are imperative to effectively address and mitigate the impact of these arboviral infections on public health worldwide.